Firm Characteristics and Compliance with IFRS 15 Mandatory Disclosures: Evidence from French Firms - Sameh Kobbi-Fakhfakh; Nesrine Belguith (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Do firm characteristics affect compliance with IFRS 15 mandatory disclosures? Motivation- IFRS 15 became mandatory for annual periods beginning on or after January 1, 2018. It introduces new revenue recognition rules compared to the legacy standards and sets extensive disclosure requirements. Focusing on compliance with IFRS 15 mandatory disclosures allows us to measure and understand firm's disclosures on a specific topic such as revenue which represents a key performance indicator for a given firm. Idea- This study examines the association between firm characteristics and compliance with IFRS 15 disclosures. Data- We selected non-financial firms listed on the French stock market index CAC all tradable. 431 firm-year observations operating in different sectors were identified and cover the 2018- 2021 period. Based on a list comprising the disclosures required under IFRS 15, we performed a content analysis of the annual reports to measure compliance level with IFRS 15 mandatory disclosures. An unweighted disclosure index was then computed. We collected data on firm characteristics from DATASTREAM database. Tools- We developed a multiple regression model with panel data including industry and year fixed effects. We used STATA software to estimate the model. Findings- Results show that the degree of compliance with IFRS 15 mandatory disclosures varies from one industry to another as well as within the same industry and firms do not fully comply with IFRS15 disclosure requirements. In addition, firm characteristics such as firm size, leverage, profitability, audit firm size, and ownership concentration seem to be key determinants of compliance with IFRS15 mandatory disclosure requirements. Contribution- Research on how firms comply with IFRS 15 mandatory disclosures is scarce. To the best of our knowledge, apart from Napier and Stadler (2020), Boujelben and Kobbi-Fakhfakh (2020), Karim and Riya (2022) and Krupova and Partac (2022), no study has investigated this research question. While these studies have provided information on the items complied with, they have advanced descriptive analyses. To the best of our knowledge, this is the pioneer study that measures compliance with IFRS 15 mandatory disclosure requirements and provides empirical evidence on firm-level determinants of compliance levels.
Keywords: M41; M42; 650; IFRS 15; compliance; mandatory; disclosure index; firm characteristics; determinants; France